Designed whole-cell-catalysis-assisted synthesis of 9,11-secosterols - Kõllo, Marek; Kasari, Marje; Kasari, Villu; Pehk, Tõnis; Järving, Ivar; Lopp, Margus; Jõers, Arvi; Kanger, Tõnis (Beilstein Journal of Organic Chemistry, 2021)
A method for the synthesis of 9,11-secosteroids starting from the natural corticosteroid cortisol is described. There are two key steps in this approach, combining chemistry and synthetic biology. Stereo- and regioselective hydroxylation at C9 (steroid numbering) is carried out using whole-cell biocatalysis, followed by the chemical cleavage of the C–C bond of the vicinal diol. The two-step method features mild reaction conditions and completely excludes the use of toxic oxidants.
Keywords: chemoenzymatic synthesis; cortisol; hydroxylation; secosterol; whole-cell catalysis

(untitled) - Li, J.; Amatuni, A.; Renata, H. (Curr. Opin. Chem. Biol., 2020)

(untitled) - Fryszkowska, A.; Peterson, J.; Davies, N. L.; Dewar, C.; Evans, G.; Bycroft, M.; Triggs, N.; Fleming, T.; Gorantla, S. S. C.; Hoge, G.; Quirmbach, M.; Timmanna, U.; et al. (Org. Process Res. Dev., 2016)

(untitled) - Carvalho, J. F. S.; Silva, M. M. C.; Moreira, J. N.; Simões, S.; Melo, M. L. S. (J. Med. Chem., 2009)

(untitled) - Contente, M. L.; Molinari, F.; Serra, I.; Pinto, A.; Romano, D. (Eur. J. Org. Chem., 2016)

(untitled) - Noack, F.; Heinze, R. C.; Heretsch, P. (Synthesis, 2019)

(untitled) - Duecker, F. L.; Reuß, F.; Heretsch, P. (Org. Biomol. Chem., 2019)

(untitled) - Enwall, E. L.; van der Helm, D.; Hsu, I. N.; Pattabhiraman, T.; Schmitz, F. J.; Spraggins, R. L.; Weinheimer, A. J. (J. Chem. Soc., Chem. Commun., 1972)

(untitled) - Koljak, R.; Pehk, T.; Järving, I.; Liiv, M.; Lopp, A.; Varvas, K.; Vahemets, A.; Lille, Ü.; Samel, N. (Tetrahedron Lett., 1993)

(untitled) - Lopp, A.; Pihlak, A.; Paves, H.; Samuel, K.; Koljak, R.; Samel, N. (Steroids, 1994)

(untitled) - Koljak, R.; Lopp, A.; Pehk, T.; Varvas, K.; Müürisepp, A.-M.; Järving, I.; Samel, N. (Tetrahedron, 1998)

(untitled) - Huang, C.-Y.; Su, J.-H.; Duh, C.-Y.; Chen, B.-W.; Wen, Z.-H.; Kuo, Y.-H.; Sheu, J.-H. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Chang, Y.-C.; Hwang, T.-L.; Kuo, L.-M.; Sung, P.-J. (Mar. Drugs, 2017)

(untitled) - He, Y.-Q.; Lee Caplan, S.; Scesa, P.; West, L. M. (Steroids, 2017)

(untitled) - Chang, Y.-C.; Lai, K.-H.; Kumar, S.; Chen, P.-J.; Wu, Y.-H.; Lai, C.-L.; Hsieh, H.-L.; Sung, P.-J.; Hwang, T.-L. (Mar. Drugs, 2020)

(untitled) - Sica, D.; Musumeci, D. (Steroids, 2004)

(untitled) - Adinolfi, R.; Migliuolo, A.; Piccialli, V.; Sica, D. (J. Nat. Prod., 1994)

(untitled) - Jäälaid, R.; Järving, I.; Pehk, T.; Lille, Ü. (Proc. Est. Acad. Sci., Chem., 1998)

(untitled) - Kuhl, A.; Kreiser, W. (Tetrahedron Lett., 1998)

(untitled) - Jäälaid, R.; Järving, I.; Pehk, T.; Parve, O.; Lille, Ü. (Nat. Prod. Lett., 2001)

(untitled) - Kongkathip, B.; Hasakunpaisarn, A.; Boonananwong, S.; Kongkathip, N. (Steroids, 2010)

(untitled) - Salvador, J. A. R.; Silvestre, S. M.; Moreira, V. M. (Curr. Org. Chem., 2012)

(untitled) - Warnke, M.; Jung, T.; Dermer, J.; Hipp, K.; Jehmlich, N.; von Bergen, M.; Ferlaino, S.; Fries, A.; Müller, M.; Boll, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Ferrandi, E. E.; Bertuletti, S.; Monti, D.; Riva, S. (Eur. J. Org. Chem., 2020)

(untitled) - Li, A.; Acevedo-Rocha, C. G.; D’Amore, L.; Chen, J.; Peng, Y.; Garcia-Borràs, M.; Gao, C.; Zhu, J.; Rickerby, H.; Osuna, S.; Zhou, J.; Reetz, M. T. (Angew. Chem., Int. Ed., 2020)

(untitled) - Acevedo-Rocha, C. G.; Gamble, C. G.; Lonsdale, R.; Li, A.; Nett, N.; Hoebenreich, S.; Lingnau, J. B.; Wirtz, C.; Fares, C.; Hinrichs, H.; Deege, A.; Mulholland, A. J.; et al. (ACS Catal., 2018)

(untitled) - Kerr, R. G.; Rodriguez, L. C.; Keliman, J. (Tetrahedron Lett., 1996)

(untitled) - Wüst, F.; Carlson, K. E.; Katzenellenbogen, J. A. (Steroids, 2003)

(untitled) - Marwah, P.; Marwah, A.; Lardy, H. A. (Tetrahedron, 2003)

(untitled) - Petrusma, M.; Dijkhuizen, L.; van der Geize, R. (Appl. Environ. Microbiol., 2009)

(untitled) - Petrusma, M.; Hessels, G.; Dijkhuizen, L.; van der Geize, R. (J. Bacteriol., 2011)

(untitled) - Kirihara, M.; Osugi, R.; Saito, K.; Adachi, K.; Yamazaki, K.; Matsushima, R.; Kimura, Y. (J. Org. Chem., 2019)

(untitled) - Quan, J.; Tian, J. (Nat. Protoc., 2011)